Evaluating EduTrack System Quality Using ISO/IEC 25010 and the DeLone and McLean Model - Syahrul; Alifya NFH; Shabrina Sinta Dewi; Dwi Rezky Anandari S (Journal of Embedded Systems, Security and Intelligent Systems, 2025)
The integration of information systems in higher education enhances efficiency, transparency, and academic service quality. However, continuous evaluation is crucial to ensure that such systems meet user expectations and comply with international quality standards. This study evaluates the quality of the EduTrack Information System developed for the Master’s Program in Educational Research and Evaluation at Universitas Negeri Makassar. Using a quantitative descriptive method, the research integrates the ISO/IEC 25010 software quality standard and the DeLone & McLean Information System Success Model. Data were collected from 60 active student users through questionnaires and technical testing with tools such as Apache JMeter, OWASP ZAP, Mozilla Observatory, K6, and the System Usability Scale (SUS). EduTrack demonstrated excellent results in functional suitability (100%), reliability (96.55%), and usability (SUS score = 71.5, good). The PLS-SEM analysis confirmed that service quality (β = 0.580) and information quality (β = 0.390) significantly affect user satisfaction (R² = 0.716). These findings indicate that EduTrack performs effectively and aligns with user expectations, though security enhancements are still required. This study demonstrates an integrated evaluation framework that combines technical quality standards and user satisfaction analysis, providing a reference model for future assessments of academic information systems.